Cowpea embryo rescue: influence of culture media composition on plant recovery from isolated immature embryos - Pellegrineschi, A.; Fatokun, C.A.; Thottappilly, G.; Adepoju, A.A. (Springer, 1997)
Factors responsible for successful rescue of immature embryos of cowpea [Vigna unguiculata (L.) Walp.] and V. vexillata (L.) and for in vitro embryo development were studied. A new basal medium for embryo development in vitro was formulated on the basis of the mineral composition of embryos. Sucrose, fructose and glucose were compared as carbohydrate sources. The highest frequency of embryos developing into plants was obtained with sucrose. Adding casein hydrolysate to the medium increased plant recovery by 30%. Among the plant growth factors used, cytokinins, zeatin, 6-benzylaminopurine and kinetin were the most effective in promoting embryo maturation and development. A method that can routinely ensure high plant recovery from cultured immature cowpea embryos is proposed.